Molecular dynamics simulation of nanoindentation in cr, al layers and al/cr bilayers, using a hard spherical nanoindenter (2014)
Three-dimensional molecular dynamics (MD) simulations of a nanoindentation technique using the hard sphere method for Cr (bcc) and Al (fcc) thin films and (Cr/Al)n (n=1,2) systems were carried out. For the model implementation, Morse interatomic potential was used for describing the single crystal interaction and the contact between Cr and Al structures. On the other hand, fixed boundary conditions were used and the repulsive radial potential was employed for modeling the spherical tip, and ideal mechanical properties at 0 K were obtained by simulating load-unload curves. Bilayers presented higher hardness and Young´s modulus than Cr and Al layers. Moreover, the region of atoms movement after the unload process shows a continuous parabolic boundary for Al and Cr layers and a discontinuous boundary for the bilayers caused by the interfaces.